Effects of Methyl Jasmonate and Putrescine on Tryptanthrin and Indirubin Production in in vitro Cultures of Isatis demiriziana Mısırdalı - Özgür Karakaş (International Journal of Secondary Metabolite)
Tryptantrin and indirubin are pharmacologically active compounds used in treatment of disseases such as cancer and Alzheimer's. In this study, we investigated the influences of different concentrations of methyl jasmonate (MeJa) and putrescine (Put) on tryptanthrin and indirubin production in leaf explants and development of Isatis demiriziana Mısırdalı grown in vitro. In all media treated with methyl jasmonate, tryptanthrin production in leaves of plantlets showed an increase. The highest increase in tryptanthrin production was observed in solid Murashige-Skoog (MS) medium containing 1.0 mM MeJa (154.026 ± 0.11 µg g-1), about 2.85-fold higher than the control (untreated plantlets) (40.017 ± 0.031 µg g-1). Production of tryptanthrin decreased about 2.56-fold in the leaves of plantlets treated with Put, when compared to control. The highest indirubin production was obtained in the leaves of plantlets grown in the MS medium containing 0.1 mM MeJa (11.274 ± 0.035 µg g-1) but treatments with Put didn’t show any positive affect on the indirubin production. Analysis of tryptanthrin and indirubin were performed using high performance liquid chromatography (HPLC).